Opportunities for Radiology Trainee Education Amid the COVID-19 Pandemic: Lessons From an Academic Breast Imaging Program - Wang, Gary X. (Acad Radiol, 2021)
The COVID-19 pandemic required restructuring of Radiology trainee education across US institutions. While reduced clinical imaging volume and mandates to maintain physical distancing presented new challenges to traditional medical education during this period, new opportunities developed to support our division in providing high-quality training for residents and fellows. The Accreditation Council for Graduate Medical Education (ACGME) Core Competencies for Diagnostic Radiology helped guide division leadership in restructuring and reframing breast imaging education during this time of drastic change and persistent uncertainty. Here, we reflect on the educational challenges and opportunities faced by our academic breast imaging division during the height of the COVID-19 pandemic across each of the ACGME Core Competencies. We also discuss how systems and processes developed out of necessity during the first peak of the pandemic may continue to support radiology training during phased reopening and beyond.